Розробка компонентів інформаційної системи із функцією підбору таргетованої реклами - Голуб, Д. К. (ХНУРЕ, 2024)
This report describes the stages of development of a social network information system that supports the function of intelligent selection of recommended advertising based on users' interests. The social network considered in this report refers to a system where users can interact with each other by creating and rating posts and comments. A system for selecting relevant advertisements consists of analysing user interests using data mining and then selecting advertisements based on this data. As an object of development, the current report considers a mechanism for selecting relevant advertisements, which is integrated at the function level into an information system with a thin client architecture that consists of a client part of a web application, a server part of a web application and a relational database.
Keywords: таргетована реклама; рекламні компоненти